Effect of permeability anisotropy on the CO2 saturation distribution and phase change during a leakage event in a saline aquifer - Guo, Chaobin; Wang, Xinwen (Frontiers in Energy Research, 2024)
Predicting impacts of potential carbon dioxide (CO2) leakage into shallow aquifers that overlie geologic CO2 storage formations is an important part of developing reliable carbon storage technology. To quantifying the effect of permeability anisotropy, a three-dimensional hypothetical reservoir model was formulated to analyze the migration behavior of CO2 under diverse permeability anisotropy scenarios. Sensitivity analyses for parameters corresponding to the permeability anisotropy and the leakage rate are conducted, and the results suggest that permeability anisotropy significantly affect the CO2 migration characteristics. Increasing the parameter of vertical/horizontal permeability ratio results in longer CO2 migration distances, which enhances the aqueous phase ratio and safety through more interaction with the aquifer, but also raises the potential of the leakage reaching the ground surface due to higher gas ratio. A comprehensive understanding of these dynamics is crucial for implementing effective monitoring and management strategies.